1990
DOI: 10.1227/00006123-199002000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Ventricular Fluid Pressure and Body Position in Normal Subjects and Subjects with Shunts: A Telemetric Study

Abstract: Using a chronically implanted telemetric pressure sensor, we have determined the quantitative relationship between changes in body position and ventricular fluid pressure in normal subjects and subjects with shunts. The method allows accurate, reliable measurement of negative as well as positive pressures. We describe the derangement of postural intraventricular pressure regulation caused by placement of a shunt, as well as the influence of various shunt systems and the antisiphon device on this problem. Ventr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
103
1
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(116 citation statements)
references
References 0 publications
8
103
1
4
Order By: Relevance
“…we may be unable to demonstrate 'true' significant differences. Another limitation is that we did not have access to 24-h monitoring data on ICP, which is known to change according to the position of the head and in the course of the day (22)(23)(24), so that it should be monitored continuously for at least 24 h to get reliable information on its mean level (25)(26)(27). The present patients were referred to our hospital when they had symptoms and signs of increased ICP and it was not considered ethically acceptable to wait for the results of continuous ICP monitoring, but rather they were operated on as soon as a diagnosis of hydrocephalus had been confirmed by other means.…”
Section: Discussionmentioning
confidence: 99%
“…we may be unable to demonstrate 'true' significant differences. Another limitation is that we did not have access to 24-h monitoring data on ICP, which is known to change according to the position of the head and in the course of the day (22)(23)(24), so that it should be monitored continuously for at least 24 h to get reliable information on its mean level (25)(26)(27). The present patients were referred to our hospital when they had symptoms and signs of increased ICP and it was not considered ethically acceptable to wait for the results of continuous ICP monitoring, but rather they were operated on as soon as a diagnosis of hydrocephalus had been confirmed by other means.…”
Section: Discussionmentioning
confidence: 99%
“…4,21 Efforts have been made to determine intracranial pressure as a relevant pathophysiological and diagnostic factor for hydrocephalus. 2,5,10,19,23 In contrast, determination of intraperitoneal pressure (IPP) as part of the preoperative assessment remains neglected and is still debated in the literature. Reported values range from subatmospheric to 15-25 cm H 2 O regardless of the intraperitoneal location, reference level, body position, and measurement technique.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…15,27 Intracranial pressure studies at different tilt angles have shown that there is a faster reduction of ICP at smaller angles and a slower reduction at higher angles. 2,8,73 In healthy subjects, with upright posture there is a drop in ICP ranging between -5 and 5 cm H 2 O with reference to the foramen magnum.…”
mentioning
confidence: 99%
“…54 In contrast, in patients harboring shunts without antisiphon devices, pressures range from -15 to -35 cm H 2 O when they are upright. 15,41,45 One method that allows us to quantify the cerebral venous pressure component of ICP during CSF diversion is Davson's steady-state formula, 23 …”
mentioning
confidence: 99%